The 2‐Propanol Fuel Cell: A Review from the Perspective of a Hydrogen Energy Economy. Issue 9 (16th July 2021) - Brodt, Matthew; Müller, Karsten; Kerres, Jochen; Katsounaros, Ioannis; Mayrhofer, Karl; Preuster, Patrick; Wasserscheid, Peter; Thiele, Simon
Abstract : The 2‐propanol fuel cell has been shown to hold several key advantages over the more established methanol fuel cell, including a comparably high real open‐circuit voltage, reduced fuel crossover through a Nafion membrane and a benign toxicological fuel profile. In addition, while the highly selective partial oxidation of 2‐propanol to acetone in a fuel cell (rather than the more typical complete combustion of organic fuels to CO2 ) has been viewed as a disadvantage in the past, recent work has shown that the 2‐propanol/acetone couple is compatible with traditional hydrocarbon liquid organic hydrogen carrier (LOHC) systems though transfer hydrogenation. With this approach, a disadvantage of hydrogen LOHC logistics—the steep energy cost of dehydrogenation that must be provided during energy‐lean times—can be largely avoided. This LOHC compatibility along with the potential for high fuel‐cell performance could place the 2‐propanol fuel cell (also referred to as the direct isopropanol fuel cell or DIFC) in a position to enable a hydrogen energy economy while avoiding the drawbacks of molecular hydrogen transport and storage. In this Review, the purpose is to ascertain the state‐of‐the‐art of DIFCs—an understudied yet promising research area with unique advantages and challenges. Abstract : 2‐Propanol fuel cells (also known as direct isopropanol fuel cells or DIFCs) convert isopropanol to acetone with very high selectivity. This Review highlights the development and state‐of‐the‐art of such devices. DIFCs may be well‐suited to play an important role in a hydrogen energy economy if technical challenges regarding long‐term operation can be solved.